The Potential Of A Third World War (WWIII) As The Implication Of The War Between Russia And Ukraine - T. Mas Turi; I Wayan Warka; Aris Sudiarto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The war between Russia and Ukraine occurred on February 24, 2022, after both sides both defended their arguments and there was a stalemate in efforts to resolve diplomatically. Finally, the path taken by the two countries in resolving the existing conflict, namely by war. Analysts and world experts predict that Russia's war with Ukraine will potentially lead to a third world war because each country involves various parties, both Ukraine, supported by NATO and Russia, supported by various countries. The purpose of this study is to analyze the potential for a third world war as an implication of the war between Russia and Ukraine. The research method used is a qualitative approach with descriptive analysis. The researcher uses the strategy theory proposed by Sun Tzu, the geopolitical theory proposed by Hayati and the theory of "The Sociology of Conflict" by George Simmel. The results of the study show that the war between Russia and Ukraine directly or indirectly has involved various countries to enter into the conflict, thus making the international community worried that there will be a bigger impact. The conclusion of this research is that the war between Russia and Ukraine has the potential to cause a third world war.